2018
DOI: 10.1371/journal.pone.0207595
|View full text |Cite
|
Sign up to set email alerts
|

Neo4j graph database realizes efficient storage performance of oilfield ontology

Abstract: The integration of oilfield multidisciplinary ontology is increasingly important for the growth of the Semantic Web. However, current methods encounter performance bottlenecks either in storing data and searching for information when processing large amounts of data. To overcome these challenges, we propose a domain-ontology process based on the Neo4j graph database. In this paper, we focus on data storage and information retrieval of oilfield ontology. We have designed mapping rules from ontology files to reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…The results obtained were included in a Neo4J graph database 28 to provide a graphical representation of miRNAs-targets interactions (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained were included in a Neo4J graph database 28 to provide a graphical representation of miRNAs-targets interactions (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Percuku et al (2017) used the Neo4j database to store the measurement data of substation, which make up for the defects of memory resource waste and poor relational adaptability of relational database when the data structure is complex. In the field of petroleum exploration and development, research showed that Neo4j database can save more than 13% memory space and promote retrieval efficiency by more than 30 times compared to relational database (Gong et al, 2018). Knowledge reuse, such as knowledge retrieval, knowledge-assisted decision-making, knowledge reasoning and so on, realizes the interaction between human and data through IT system.…”
Section: Knowledge Graph Applicationsmentioning
confidence: 99%
“…Experimental results indicate that an increase in temperature can sufficiently convert a perfect LoRa link into an almost useless link, and that different Port Physical Layer (PHY) settings of LoRa exert different effects on temperature fluctuations [29]. Cattani et al reduced the size of packet fragments to improve the reliability of communications in duty-limited networks [30]. The reliability of communication is reflected by the energy consumption, throughput, and end-to-end delay.…”
Section: Related Workmentioning
confidence: 99%